Factors affecting undergraduate students' academic performance / Sylvia @ Nabila Azwa Ambad, Faiqah Mawardi and Mohammad Firdaus Mohamad - Azwa Ambad, Sylvia Nabila; Mawardi, Faiqah; Mohamad, Mohammad Firdaus (2017)
The end results of educational process have shown that a large number of students failed to maintain a high degree of academic excellence. These failures could be due to many factors such as the students themselves, teaching and learning styles employed by the lecturers, and the university support system, among others. Thus, the aim of this study is to identify the determinant of academic performance among undergraduate students in UiTM Sabah. This aim is in line with the vision of UiTM, to generate outstanding scholars, academic excellence, and world-class standards in order to produce competitive graduates. At the same time, this study could assist the university to achieve its' quality objective, which is to ensure 90% of the undergraduate students will graduate on time. 306 students were randomly selected as samples and the questionnaires were distributed through online and face-to-face survey during class. In the questionnaire, the students were asked about their opinions on lecturers' teaching method, their attitude towards learning, and the perceived social support from family and friends in relation to their academic performance. The data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0. The results of this study indicate that all hypotheses were supported. The students' attitude was the most significant predictor of academic performance. Furthermore, the results are beneficial to the university and lecturers as a guideline to execute appropriate teaching and learning method so as to unleash the students' full potential. Subsequently, it will help to achieve UiTM's vision and quality objectives.